Optimal delegation and information transmission under limited awareness - Sarah Auster; Nicola Pavoni (Theoretical Economics, 2024)
We study the delegation problem between a principal and an agent, who not only has better information about the performance of the available actions but also superior awareness of the set of actions that are actually feasible. We provide conditions under which the agent finds it optimal to leave the principal unaware of relevant options. By doing so, the agent increases the principal's cost of distorting the agent's choices and increases the principal's willingness to grant him higher information rents. We further show that the principal may use the option of renegotiation as a tool to implement actions that are not describable to her at the contracting stage. If the agent renegotiates, his proposal signals information about the payoff state. Due to her limited awareness, the principal makes a coarse inference from the agent's recommendations and, as a result, accepts a large number of the agent's proposals, which ultimately benefits both.
Keywords: D82; D83; D86; 330; optimal delegation; renegotiation; Unawareness